Quantification of Cr in Lu1-xSrxFe0.5Cr0.5O3 (0 ≤ x ≤ 1) samples containing impurities using X-ray techniques in combination with several data treatment methodologies. (October 2021) - Lurgo, Florencia E.; Limandri, Silvina; Carbonio, Raúl E.; Tirao, Germán
Abstract: Wet chemical method was applied with the intention of obtaining Lu1-x Srx Fe0.5 Cr0.5 O3 (0 ≤ x ≤ 1) perovskites in polycrystalline form. A systematic study of the crystal structure of the main perovskite phase obtained as well as a characterization of impurities was performed by X-ray techniques: powder diffraction (PXRD), high resolution emission spectroscopy (HR-XES), and photoelectron spectrometry (XPS). The PXRD data of Lu1-x Srx Fe0.5 Cr0.5 O3 (0 ≤ x ≤ 1) were refined using Pbnm orthorhombic unit cell for the perovskite structure. Only samples with x = 0 and x = 0.1 resulted pure; as the amount of Sr increases, it is segregated as impurities, first as SrCrO4 and then as SrFe12 O19 . The mean oxidation state of Cr in the analyzed samples was obtained from HR-XES by quantifying spectral changes in the Cr-Kβ" and Cr-Kβ2, 5 regions by different methodologies: statistical parameters and multivariate methods. The results were compared with the ones obtained by PXRD and XPS. With the last technique Cr 6+ ionic concentrations were obtained through the spectral analysis in the region Cr2p3/2 –580eV. Similar Cr 6+ ionic compositions were obtained using the three X-ray techniques. Graphical abstract: Image 1 Highlights: Global characterization of novel perovskite was performed by X-ray techniques. Cr chemical environment study were made using several XES processing methodologies. Cr oxidation state was obtained by spectral changes in Kβ" - Kβ2, 5 regions. XES and XPS allowed impurity phases quantification by Cr 6+ determination.